2005
DOI: 10.1007/s00520-005-0820-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of dietary supplements in a community hospital comprehensive cancer center: implications for conventional cancer care

Abstract: In our study, twenty-five percent of patients receiving chemotherapy were concurrently using dietary supplements suspected to have adverse interactions with chemotherapy, usually relying on information sources other than healthcare professionals. Given the prevalence rates of these agents, healthcare providers should systematically inquire about them, and consider the potential for drug-dietary supplement interactions in treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 18 publications
2
53
0
2
Order By: Relevance
“…Colorectal and breast cancer patients, in particular, seem to be likely to use dietary supplements, compared with lung cancer patients [51,52]. An increased perception of the risk of cancer recurrence and cancer-related death are associated with CAM use by breast cancer patients, as concluded in a study by Rakovitch et al [52].…”
Section: Reasons For Cam Usementioning
confidence: 97%
“…Colorectal and breast cancer patients, in particular, seem to be likely to use dietary supplements, compared with lung cancer patients [51,52]. An increased perception of the risk of cancer recurrence and cancer-related death are associated with CAM use by breast cancer patients, as concluded in a study by Rakovitch et al [52].…”
Section: Reasons For Cam Usementioning
confidence: 97%
“…The results obtained do not coincide with similar research conducted in the USA and Turkey, which is probably due to the different geographical location and regional traditions in the use of herbal preparations. 5,6 Herbalism is perceived by patients as a natural and safe method of treatment, as shown in the research in which more than half of the respondents recognized that the herbal preparations are safer (34.8%) or rather safer (27.2%) compared to synthetic drugs. A study conducted among doctors from 16 countries of the Middle East, showed that herbal dietary supplements and herbal OTC medicines are the most commonly used addition to pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Plant raw materials most commonly used by cancer patients are: garlic, nettle, thyme, ginger, milk thistle, echinacea, ginko, ginseng and valerian. 5,6 Literature data indicates a potential antitumor activity of substances of vegetable origin, of which the most frequently cited are curcumin, resveratrol, artemisinin, berberine, piperine, mistletoe, green tea, broccoli. 7 Conventional drug therapy combined with complementary medicine are increasingly used in cancer patients treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority (53%) of patients using dietary supplements during recent chemotherapy did not seek advice or guidance from a medical provider [7]. Disclosure, even if done, may be incomplete.…”
mentioning
confidence: 99%